Concern Based Adoption Model (CBAM) Dalam Implementasi Kurikulum Program Pendidikan Vokasi (Jurnal Pendidikan Teknik Mesin, 2005)
Education quality improvement especially teaching in vocational program depends on how curricullum is designed, implemented, and evaluated. Curricullum implementation model with CBAM gives benefits since curricullum is new skills to both students and teachers. Innovation appears when there is connection with variant life in society. Model analysis that is implemented through diagnosis, application, and evaluation simutanously, afect both students' and teachers' creativity development.